2010
DOI: 10.1002/jmri.22393
|View full text |Cite
|
Sign up to set email alerts
|

Divergent neural processes specific to the acute and sustained phases of verum and SHAM acupuncture

Abstract: Purpose: To discuss which brain region potentially functioned and switched between the immediate and delayed response of acupuncture. Materials and Methods:A nonrepeated event-related functional MRI (fMRI) design was used to investigate the spatial and temporal patterns of acupuncture effects induced by needling an acupoint ST36 (ACU) and a nonmeridian point (SHAM). The standard general linear model was used to detect the immediate neural responses of acupuncture. Graph theory analysis was used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
(73 reference statements)
3
31
1
Order By: Relevance
“…One intriguing finding here is the increased degree of connectivity recorded by sensors overlying the left temporal cortex within the delta, theta and gamma bands. Compared to recent fMRI studies in which the temporal gyrus as well as the underlying amygdala and hippocampus were indicated as network hubs following verum acupuncture, with the advantage of MEG we observed that such modulation effects existed specifically within the above-mentioned three bands, among which delta was the most dominant [58], [59]. Another thought-provoking result is that in addition to previous investigations which illustrated enhanced interactions of the temporal gyrus with the frontal gyrus and prefrontal cortex following acupuncture either at ST36 or NAP, we further pinpointed that such an effect occurred only in the delta band for sham acupuncture, compared with the additional modulation effect in the beta band of the verum group [60].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…One intriguing finding here is the increased degree of connectivity recorded by sensors overlying the left temporal cortex within the delta, theta and gamma bands. Compared to recent fMRI studies in which the temporal gyrus as well as the underlying amygdala and hippocampus were indicated as network hubs following verum acupuncture, with the advantage of MEG we observed that such modulation effects existed specifically within the above-mentioned three bands, among which delta was the most dominant [58], [59]. Another thought-provoking result is that in addition to previous investigations which illustrated enhanced interactions of the temporal gyrus with the frontal gyrus and prefrontal cortex following acupuncture either at ST36 or NAP, we further pinpointed that such an effect occurred only in the delta band for sham acupuncture, compared with the additional modulation effect in the beta band of the verum group [60].…”
Section: Discussioncontrasting
confidence: 75%
“…Acupuncture-induced modulations on functional connectivity have already been illustrated in previous fMRI investigations [58], [59], [60]. Given that fMRI is naturally an indirect imaging tool, we attempted to seek whether or not such alterations would be directly observed using an electrophysiological imaging modality, among which MEG being the most suitable for estimating functional connectivity [40], [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that acupuncture not only regulates the functional state and connectivity of sensorimotor areas of normal people [9], [14], [29] but also affects the functional state of the bilateral sensorimotor cortex of stroke patients [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…24 Acupuncture points were chosen in consideration of studies on functional brain imaging research that link activation in the cerebellum with stimulation of pelvic limb points. 25,26 These areas were chosen to neuromodulate cerebellar activity given the role of the cerebellum and its role in balance and coordination.…”
Section: Discussionmentioning
confidence: 99%